The Current Landscape of Clinical Trials for Systemic Treatment of HCC - Foerster, Friedrich (Cancers (Basel), 2021)
SIMPLE SUMMARY: Liver cancer is a life-threatening disease. Apart from surgery and catheter-guided therapies, drugs are a central pillar for its treatment. Clinical trials are research studies that are designed to evaluate the treatment effect of a given drug. Therefore, they are the driving force behind innovation and medical progress. One such innovation in the past years has been immunotherapy, which has become increasingly important for treating cancer. Recently, the first such therapy has been approved for the treatment of liver cancer. Current clinical trials are exploring the benefit of immunotherapy and other therapies for this disease. This article gives an overview of such trials paying attention to the different underlying treatment strategies and the varying clinical settings, depending on the stage of the disease. ABSTRACT: The clinical development of systemic treatments for hepatocellular carcinoma (HCC) has gained significant momentum in recent years. After the unexpected failure of the phase 3 trials testing the PD1-inhibitors nivolumab and pembrolizumab as monotherapy in advanced HCC, a multitude of trials employing different agents in various combinations and at different disease stages have been initiated. The first positive results reported for the combination of atezolizumab and bevacizumab, as the first line treatment of advanced HCC, will bring lasting change to the management of HCC and has increased the odds of success for alternative combination therapies. This review article seeks to provide clarity on the complex and evolving landscape of clinical trials on systemic treatments of HCC. It covers current trials which test various systemic treatments (i) in the first and second line in advanced HCC, (ii) in intermediate HCC, (iii) as adjuvant as well as (iv) neoadjuvant strategies, and (v) including immune interventions other than immune checkpoint inhibition.